Jean-Jacques Rousseau e os perigos da corrupção política na República - Alves, Vital Francisco Celestino (2017)
This research takes on the challenge of linking Jean-Jacques Rousseau to the republican tradition by a common thread: political corruption. For this, it is assumed that corruption is a problem of extreme gravity and importance for political regimes in general, especially the republican regime. Arguing that that problem has been intrinsically linked to the discussions prompted by this tradition since ancient times, was revisited in the Renaissance, is present in republican thinking in the Enlightenment, and continues to threaten contemporary political regimes; this study, initially, briefly maps how its object of research appears in the reflection of the leading exponents of the republican strain, throughout the history of philosophy, in order to prepare the ground to defend the thesis that political corruption is a serious danger to the Republic. Hence, the study of the latency of corruption in the Republic – analyzed and discussed based on the rousseauist theoretical edifice – provides evidence linking the Genovese author with the Republican line. In examining the reasons why corruption is a harmful problem for the Republic, this research offers its share for placing Rousseau in the lineage of Republican thinking, as, in seeking to accomplish our goal, we examine other notions and concepts we consider appropriate for reflection on the risks of political corruption for the Republic.